P32 Quantifying levels of physical activity in patients with copd: a us cross-sectional survey. (15th November 2017) - Ding, B; Judge, D; Small, M; Bent-Ennakhil, N; Siddiqui, S
Abstract : Introduction and Objectives: Physical inactivity can increase the burden of COPD and is a predictor of mortality and hospitalisations. There has been a paucity of data examining the relationship between physical activity and COPD treatment regimen. This study aimed to describe self-reported physical activity levels according to standard of care medication class(es) in COPD. Methods: Multicentre, cross-sectional, observational survey (Study: D5970R00003) conducted in the US. Patients (≥40 years) with a physician-confirmed diagnosis of COPD completed a questionnaire that included the Functional Performance Inventory-Short Form (FPI-SF) to assess physical activity (32 items/6 domains, rated from 1= much  difficulty to 3= no  difficulty). Investigators provided information on treatment history. Results: 1775 patients participated (71.9% Caucasian, 55.1% male, 87.1% current/ex-smokers, mean age 65.2 years, mean BMI 27.5 kg/m 2 ). 14.8% of patients were classed as GOLD 2017 group A, 46.6% in group B, 2.6% in group C and 36.0% in group D. Activity impairment based on FPI-SF scores was seen in patients across all treatment classes (Table), with the greatest impairment observed in patients receiving triple therapy and in the FPI-SF domains requiring most physical activity ('maintaining the household' and 'physical exercise'). Conclusions: Patients with COPD who required triple therapy tended to report the lowest levels of physical activity. Longitudinal studies are needed to evaluate the effect of bronchodilator treatment on the relationship between lung function, COPD symptom burden and physical activity.